Design and evaluation of controlled release mucoadhesive microspheres of amoxicillin for anti Helicobacter pylori therapy - Venkateswaramurthy, N; Sambathkumar, R; Perumal, P (Asian Journal of Pharmaceutics (AJP), 2014)
The aim of this study was to develop controlled release mucoadhesive microspheres of amoxicillin trihydrate for the treatment of peptic ulcer disease caused by Helicobacter pylori (H. pylori). Microspheres were prepared by solvent evaporation technique using carbopol 974P, hydroxypropyl methyl cellulose K4M (HPMC K4M) and Eudragit RS 100. The prepared microspheres were subjected to evaluation for particle size, incorporation efficiency, in vitro mucoadhesion and in vitro drug release characteristics. Absence of drug-polymer interaction was confirmed using differential scanning calorimetry analysis and fourier transform infrared spectrophotometry. The prepared microspheres showed a strong mucoadhesive property. The polymer concentration influenced the in vitro drug release significantly in 0.1N HCl. The particle sizes of systems ranged between 123±8.35 μm and 524±11.54 μm. Percent drug entrapment and release profiles of amoxicillin trihydrate in 0.1 N HCl were determined using high-performance liquid chromatography.The percentage drug entrapment and percentage yield of formulations were about 56.71±1.66% to 88.32±0.65% and 39.20±1.62% to 92.40±1.32%, respectively.The stability of the drugs was assessed in 0.1 N HCl. The results further substantiated that mucoadhesive microspheres improved the gastric stability of amoxicillin trihydrate (due to entrapment within the microsphere). From the above results, it was concluded that the mucoadhesive microspheres of amoxicillin trihydrate has feasibility for eradicating H. pylori from the stomach more effectively because of the prolonged gastrointestinal residence time and controlled release of drug from the formulation.